Virologic, immunologic and clinical responses in foreign-born versus US-born HIV-1 infected adults initiating antiretroviral therapy: an observational cohort study. - Deidra D Parrish (Public Library of Science (PLoS), 2012)
Introduction Mortality rates within the first year of combination antiretroviral therapy (cART) initiation are several-fold higher in resource-limited countries than in resource-replete settings. However studies in western countries examining virologic, immunologic and clinical responses after cART initiation in indigenous versus non-indigenous populations have shown mixed results. This study aimed to determine whether there is a difference in these outcomes in a United States setting between foreign-born and US-born patients. Methods This retrospective observational cohort study of HIV-1 infected adults in one urban clinic in the United States compared virologic suppression, immune recovery and rates of AIDS defining events (ADEs) within the first year of cART using linear mixed effect models, log rank tests and Cox proportional hazard models. Data were analyzed for 94 foreign-born and 1242 US-born patients. Results Foreign-born patients were younger (31.7 years versus 38.5 years), more often female (38.3% versus 27.1%), less often injection drug users (3.2% versus 9.5%) or men who have sex with men (19.0% versus 54.5%), and had higher loss to follow-up rates (14.9% versus 6.2%). No significant differences were detected between the groups in suppression of plasma HIV-1 RNA, CD4+ cell recovery or development of ADEs. Conclusions During the first year on cART, virologic suppression, immune recovery and development of ADEs were comparable between foreign-born and US-born patients in care in a US clinic. Differential rates of loss to follow-up warrant further investigation in the foreign-born population.